The relationship between mental fatigue and shooting performance over the course of a National Collegiate Athletic Association Division I basketball season - Daub, B. D.; McLean, B. D.; Heishman, A. D.; Peak, K. M.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2024)
The aim of this investigation was to examine the presence of mental fatigue and concurrent changes in shooting performance across various experimental weeks throughout a National Collegiate Athletic Association (NCAA) basketball season. Fifteen elite male NCAA Division I collegiate basketball players (age 20.2 ± 1.2 years, height 199.3 ± 7.1 cm, and body mass 93.1 ± 8.6 kg) volunteered for this study. Mental fatigue and basketball shooting performance was evaluated at 4 timepoints with varying seasonal demands: high game volume (GAME), high academic load (ACADEMIC), no games and no academic load (PRACTICE), and standard number of games and academic requirements (TYPICAL). Subjective mental fatigue increased significantly (p = 0.05) from Pre to Post brief psychomotor vigilance test (PVT-B) measurements at the end of the ACADEMIC week (p = 0.002, d = 1.51) and from beginning to end of the ACADEMIC week (p < 0.001, d = 2.21). Ratings of mental effort were significantly increased during the ACADEMIC week (p < 0.001, d = 1.67). Recovery stress questionnaire (REST-Q) showed significant differences between week GAME and ACADEMIC with an increase in Social Stress (p = 0.001, d = 0.84), Fatigue (p = 0.021, d = 1.12), Disturbed Breaks (p = 0.024, d = 0.57), and Emotional Exhaustion (p = 0.035, d = 0.75). Lower shooting performance was observed during the ACADEMIC week from Pre to Post (p = 0.009, d = 0.35) and higher scores Pre to Post in the TYPICAL week (p = 0.008, d = 0.25). Basketball shooting performance was significantly reduced after increased levels of mental fatigue stemming from added academic stress. In addition, an increase in sport-specific training or games had no effect on subsequent basketball shooting performance. Special consideration should be given by coaches around examination periods because the existence of academic stressors can influence basketball shooting performance.